Micro-crack characterization for metal-on-metal hip implant of textured surface using electrical discharge machining - Hashim, Nor Liyana Safura (2020)
In hip implant, it has been proven that surface texturing which is also known as dimples can improve the lubrication performance and reduce friction. However, little attention is paid to the effect of textured surface by assessing the crack formation on the dimple areas. This research focuses on the formation of cracks on dimple edges during manufacturing process using electrical discharge machining (EDM) as higher stress is produced in this area. The crack formation then was observed during operational use of metal-on-metal (MoM) hip implant in the case that the dimples parameters are not fully optimized. For dimple manufacturing on a S45C mild steel material, machining angles was varied at 50°, 70° and 90° using developed workpiece positioning system in this research. The pulse currents were set at 1 A, 2 A and 3 A. Cracks formed on the dimple edge after the machining were observed using Scanning Electron Microscope (SEM) and measured in terms of its length. Then, nine dimples were machined on the samples of acetabular cup part using the chosen EDM parameters. Friction screening on the hip implant samples with femoral head of 28 mm diameter and radial clearance of 30 pm was carried out using four-ball bearing machine. The loads varied up to 250 N, 500 N and 1000 N representing the loading gait in the hip joint. The formation of cracks on the dimple edges for each load was then observed. The experimental results showed that when lowest current 1A was applied, the micro-cracks total length appeared during EDM process increased substantially. For MoM hip implant, it was found that the optimal setting for the EDM machining was 3 A at 90° machining angle, taking into account the curved hip implant surface. However, more than 50% of the cracks formed during machining were removed after loading due to surface grooving. It is suggested that it is suitable to machine the dimples on the hip implant surface using EDM in terms of crack formation. While new cracks formed after the loading were found to be far more dominant than the original cracks due to EDM machining. The cracks were found to be much wider and longer especially with the imposition of the maximum load of 1000 N. The contribution of this study is on the effect of crack formation on hip implant improvement, as well as providing basic data of textured surface in hip implant. This is because the crack formed can cause wear and friction which can lead to wear fatigue in hip implant thus shorten lifespand its lifespan.